Coping with waves and stress: a jobs-demands resources model analysis of seafarers' mental health post COVID-19 - Lim, Elaine Kai Ting (Nanyang Technological University, 2023)
Purpose – The purpose of this study is to understand how COVID-19 affects seafarers’ mental health and to devise measures to address them. Seven factors that the paper will be focusing on includes environment, job stressors, job strains, job resources, job satisfaction, burnout, and turnover intention.